-2(x - 5) + 4(9 + x)
-2x + 10 + 36 + 4x
=2x + 46
Answer:
The expression which is equivalent to –2i(6 – 7i) is; (0 – 2i)(6 – 7i)
Answer:
2
Step-by-step explanation:
If you look at how many lines are lines up at the ten that is the answer
ok I will help u tomorrow I am busy today
Answer:
Graph 1 is not proportional
Graph 2 is proportional - y is 2 times x
Step-by-step explanation:
In graph 1, there is no x-y correlation
In graph 2, there is, when x=1, y=6
when x=2, y=12. Therefore, when x=3 y would equal 18.